The Impact of Berberine on Intestinal Morphology, Microbes, and Immune Function of Broilers in Response to Necrotic Enteritis Challenge. (19th October 2021) - Yuan, Lin; Li, Mengjie; Qiao, Yingying; Wang, Haoyu; Cui, Litong; Wang, Mingfa
Abstract : The objective of this study was to explore the therapeutic effects of berberine on necrotic enteritis (NE) in broilers caused by Clostridium perfringens . A total of 240 1-day-old Arbor Acres chicks were divided into four groups, as negative controls (NC), positive controls (PC), berberine- (BER-) treated, or lincomycin- (LMY-) treated groups. Broilers were challenged with C. perfringens at 15-21 days of age, followed by BER or LMY supplied in drinking water for 7 days. Experimental results showed that C. perfringens infection significantly decreased growth performance and increased intestinal necrosis index and the number of C. perfringens present to 6.45 Log10 CFU/g (P < 0.001 ). Proinflammatory cytokines in the ileum were significantly increased, but the expression of ileal tight junction proteins occludin and claudin-1 was significantly reduced. Both BER and LMY ameliorated some of these observations. Compared with the PC group, the number of C. perfringens in the cecum was significantly decreased following treatment (P < 0.001 ), and growth performance and small intestine morphology were similar to those of the NC group (P > 0.05 ). IL-1 β, IL-6, and TNF- α levels as well as occludin and claudin-1 expression were also significantly improved (P < 0.05 ). BER has the potential to replace antibiotics for NE caused by C. perfringens .